Editorial: Towards a psychophysiological approach in physical activity, exercise, and sports, volume III - Forte, Pedro (2024)
“Towards a psychophysiological approach in physical activity, exercise, and sports-volume III” explores the complex interactions between physical activity, exercise, and psychological factors in various populations and analytical contexts. A recurring theme across studies is the emphasis on how psychological factors, such as anxiety, self-confidence, and attentional control, interact with physiological outcomes like heart rate variability (HRV) and perceived exertion. Key findings include the enhancement of performance through strategic psychological interventions (e.g., mindfulness, positive thinking) and the understanding that physical activity can alleviate mental health symptoms, especially in populations with chronic conditions such as long COVID. The studies also collectively underscore the importance of a holistic approach to optimizing performance in individual and team sports, where psychological wellbeing plays a crucial role in optimizing physical outcomes.